Family Outcomes for Families of 4–5-Year-Old Children on the Autism Spectrum Who Have Received Early Childhood Intervention in Australia. Issue 3 (July 2019) - Adams, Dawn; Keen, Deb; Heussler, Helen S.; Wicks, Rachelle; Roberts, Jacqueline
Abstract : Early childhood intervention (ECI) services for children on the autism spectrum commonly espouse a family-centered approach but outcomes studies often focus solely upon the child. Mothers of 96 children on the spectrum (aged 4–5 years) completed a measure of access to ECI and the Family Outcomes Survey—Revised. Family outcomes after ECI were generally positive, although a notable proportion of mothers rated that their child still did not participate in social, recreational, or religious activities that they would want to (15.6%) and that as parents, they did not know about post-ECI options (14.6%). Family outcomes and perceived helpfulness of ECI did not differ with demographic data with the exception of Accessing the community subscale, which was significantly higher in families with incomes above AUD$80, 000.